Em cena: o ensino de ciências com cinema na perspectiva de pesquisadores - Lazzarin, Ariane Andressa (2021)
Since its invention, cinema has been thought in relation to education. Assuming this, the aim of this investigation was to carry out an analysis about the use of cinema within the school environment. More precisely, this research has focused on the understanding about the possibilities of using (or not) the cinema as a resource for teaching and learning science’s concepts and themes. Firstly, we discuss what cinema means in the context of this research, and its relationship with education. Next, we present a systematic review on the subject, based on an examination in the CAPES database, in the Google Scholar tool, and also in sources from the references of the documents studied. The results were analysed according to the guidelines of the Discursive Textual Analysis (ATD). The discussion of the data was led by four guiding questions that lately also channelled the reflection and composition of the metatext, namely: 'How is it used?', 'What is it used for?', 'Why is it used?', and ' Why is it not used? '. Through the first question, we presented three final categories that depict the working methodologies with cinema. With the second one, we arrived at three final categories related to the main objectives and goals when using such a resource. In the third question, we discussed two categories that explain the reasons, motivations and expectations that led teachers to use this resource. Finally, the fourth question helped us to understand, based on two categories, the limitations that would hinder or prevent the use of cinema in the classroom. Grounded on these results, we developed a reflection primarily guided by the ideas of Vigotski (2018), which allowed us to point out the emergence of some elements that were discussed in the last chapter. Among them, we highlight the emotional character of cinema, the necessity and importance of the teacher’s mediation, the plurality of strategies, reasons and objectives for the cinema’s use, and the misguided blaming of the teacher who chooses not to use the cinema didactically. In this way, we exposed understandings and concerns that indicate the presence of educational characteristics in the cinema for teaching, particularly here, of science.